SNX30 inhibits lung adenocarcinoma cell proliferation and induces cell ferroptosis through regulating SETDB1 - Xinjie Fan; Qichu Zhu; Chengzhuo Du; Jinlai Chen; Yingming Su (Journal of Cardiothoracic Surgery)
Abstract Background Lung adenocarcinoma is the most common form of lung cancer and one of the most life-threatening malignant tumors. Ferroptosis is an iron-dependent regulatory cell death pathway that is crucial for tumor growth. SNX30 is a key regulatory factor in cardiac development; however, its regulatory mechanism and role in inducing ferroptosis in lung adenocarcinoma remain unclear. Objective This study aimed to elucidate the functions and specific mechanisms of action of SNX30 in lung adenocarcinomas. Methods SNX30 levels in lung adenocarcinoma cell lines (A549 and HCC827) were determined using reverse transcription quantitative real-time PCR (RT-qPCR) or western blotting. Cell proliferation and apoptosis were assessed by CCK8 and flow cytometry, respectively. The intracellular levels of total iron and Fe2+ were detected using Iron Assay Kits. Reactive oxygen species (ROS) levels were evaluated using a DCFH-DA probe and flow cytometry. Cysteine (Cys), glutathione (GSH), and glutathione peroxidase 4 (GPX4) levels were measured using detection assay kits. Other related markers, including Ptgs2, Chac1, SETDB1 cleaved-Caspase3, and Caspase3 were analyzed by RT-qPCR or western blotting. Results SNX30 is downregulated in lung adenocarcinoma cell lines. SNX30-plasmid depressed lung adenocarcinoma cell proliferation, accelerated apoptosis, enhanced cleaved-Caspase3 expression and cleaved-Caspase3/Caspase3 ratio. Ferrostatin-1 significantly reversed the effects of the SNX30-plasmid on cell ferroptosis in lung adenocarcinoma, as confirmed by the reduced ROS levels, inhibited intracellular total iron and Fe2+ levels, decreased Ptgs2 and Chac1 expression, and increased Cys, GSH, and GPX4 release. We observed that the level of SETDB1 was lower in the SNX30-plasmid group than in the control-plasmid group, whereas the opposite results in ferrostatin-1 treated cells. SNX30 negatively regulates SETDB1 expression in lung adenocarcinoma cells. The upregulation of SETDB1 reversed the effects of the SNX30-plasmid on ferroptosis in lung adenocarcinoma cells. Conclusion SNX30 inhibits lung adenocarcinoma cell proliferation and induces ferroptosis by regulating SETDB1 expression.